EKSPLORASI PEMBELAJARAN FIQIH BERBASIS HANDPHONE DI ERA DIGITAL STUDI DI MADRASAH ALIYAH NW MENGKURU NUSA TENGGARA BARAT - Sayuti, Lalu; Silfia Hanani; Zulfani Sesmiarni (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
The use of cellphones as a Fiqh learning tool at Madrasah Aliyah NW Mengkuru, West Nusa Tenggara, has experienced significant developments since previous research. This research explores the implementation of cellphone-based Fiqh learning at Madrasah Aliyah NW Mengkuru, West Nusa Tenggara, in facing the challenges of the digital era. The research uses a qualitative approach with data collection techniques through observation, interviews and document analysis. Research subjects include Fiqh teachers and students involved in this learning program. The research results show that the use of cellphones in Fiqh learning provides benefits such as faster and more interactive material accessibility. However, the research also identified several challenges such as monitoring appropriate use and adapting the curriculum. This research contributes to understanding effective strategies for integrating technology in religious learning at Madrasah Aliyah, answering the need for learning approaches that are relevant to current conditions. This novelty makes an important contribution in updating religious learning strategies that are responsive to the dynamics of technology and educational needs today.